460 Access to Thrombectomy Capable Stroke Centers in the US: Current Geographic Patterns and Economic Disparities. (1st April 2022) - Waqas, Muhammad; Levy, Bennett; Baig, Ammad; Cappuzzo, Justin M.; Monteiro, Andre; Mullin, Wallace; Davies, Jason; Snyder, Kenneth V.; Levy, Elad I.; Siddiqui, Adnan H.
Abstract : INTRODUCTION: In the last five years, mechanical thrombectomy has revolutionized the standard of care for patients suffering from acute stroke. The mechanical thrombectomy procedures for removal of clot from large vessel of the brain has been shown to be cost effective compared to the traditional medical therapy. Given the fact that clinical outcomes are strongly dependent on time to recanalization, it is important to examine the socioeconomic disparity of geographic living distance from thrombectomy capable stroke centers (TCC) as related to patient outcomes. METHODS: The data on the US population and geographic location of thrombectomy capable stroke centers was obtained from the US Census Bureau and the websites of accrediting agencies and state governments. Using previously validated methods we estimated the population with 1 hour access to TCC. We additionally acquired median household income data for each state in the US. The proportion of population with 1 hour access to TCC was compared between low, middle and high median household states. RESULTS: There was a total of 316 TCCs in the analysis, and approximately 65% of all US residents have within one-hour access to a specialized stroke center by way of air or ground. The states with >50% of the population having less than 1-hour access to thrombectomy centers, had the average median income was nearly 10, 000 more when compared to states with <50% of the population with 1-hour access to TCC. In high-income states, 69.0% of the population had one-hour access to TCCs. In the middle-income states, 49.5 % of the population had one-hour access to TCCs, while only 21.4 % states one-hour access to TCCs, p-value = 0.01. A positive and significant relationship between economic status and percentage population with one-hour access was observed (r = 0. 44, p-value = 0.01). CONCLUSION: One-hour access to thrombectomy capable stroke centers is available to 65% of the US residents. A positive and significant relationship between economic status and percentage population with one-hour access was observed.